An Overview of Florida Sugarcane - Leslie E. Baucum; Ronald W. Rice; Tom J. Schueneman (EDIS)
Revised! SS-AGR-232, an 8-page illustrated fact sheet by L. E. Baucum and R. W. Rice, answers the most frequently asked questions about the commercial Florida sugarcane industry and describes the production of sugarcane and sugar. Published by the UF Department of Agronomy, August 2009.